Serum iron status is associated with all-cause mortality in metabolic dysfunction-associated steatotic liver disease: a prospective, observational study - Xia, Ting; Ni, Jie; Ni, Yuqin; Wu, Xinhui; Du, Kangming; Wan, Xuemei; You, Xuli (Frontiers in Endocrinology, 2024)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is the leading chronic liver disease worldwide. Emerging evidence suggests a close crosstalk between iron status and metabolic syndrome. Therefore, this cohort study aimed to investigate the relationship between serum iron status and all-cause mortality in individuals with MASLD. A total of 3393 subjects with MASLD identified by ultrasound from the Third National Health and Nutrition Examination Survey (NHANES III) were included in the analysis. Iron status indicators included serum iron, ferritin, transferrin saturation, total iron binding capacity, hemoglobin concentration, mean corpuscular hemoglobin, mean corpuscular volume, and mean corpuscular hemoglobin concentration. Cox proportional hazards models and restricted cubic spline models with adjustment for multiple confounders were applied.Stratified analyses were performed by sex and age. During a median of 26.08 years of follow-up, high serum iron and transferrin saturation were significantly associated with reduced all-cause mortality in a linear pattern (P overall<0.001). Compared with the lowest quartile, individuals with serum iron and transferrin saturation in the third or fourth quartile intervals had a 20-40% reduction in long-term mortality. However, there was no independent association of serum ferritin, total iron binding capacity, and red blood cell indices with all-cause mortality in MASLD. In conclusion, this study suggests that serum iron and transferrin saturation have the potential to serve as independent biomarkers of all-cause mortality in patients with MASLD and implies the therapeutic potential of modifying iron status.